Modeling Asymmetric Flow of Viscoelastic Fluid in Symmetric Planar Sudden Expansion Geometry Based on User-Defined Function in FLUENT CFD Package. (22nd July 2013) - Zheng, Zhi-Ying; Li, Feng-Chen; Yang, Juan-Cheng
Abstract : Through embedding an in-house subroutine into FLUENT code by utilizing the functionalization of user-defined function provided by the software, a new numerical simulation methodology on viscoelastic fluid flows has been established. In order to benchmark this methodology, numerical simulations under different viscoelastic fluid solution concentrations (with solvent viscosity ratio varied from 0.2 to 0.9), extensibility parameters (100 ≤ L 2 ≤ 500 ), Reynolds numbers (0.1 ≤ Re ≤ 100 ), and Weissenberg numbers (0 ≤ W i ≤ 20 ) are conducted on unsteady laminar flows through a symmetric planar sudden expansion with expansion ratio of 1 : 3 for viscoelastic fluid flows. The constitutive model used to describe the viscoelastic effect of viscoelastic fluid flow is FENE-P (finitely extensive nonlinear elastic-Peterlin) model. The numerical simulation results show that the influences of elasticity, inertia, and concentration on the flow bifurcation characteristics are more significant than those of extensibility. The present simulation results including the critical Reynolds number for which the flow becomes asymmetric, vortex size, bifurcation diagram, velocity distribution, streamline, and pressure loss show good agreements with some published results. That means the newly established method based on FLUENT software platform for simulating peculiar flow behaviors of viscoelastic fluid is credible and suitable for the study of viscoelastic fluid flows.